2003
DOI: 10.1385/bter:94:1:79
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron(II) Salts and Iron(III) Complexes on Trace Element Status in Children with Iron-Deficiency Anemia

Abstract: Iron-deficiency anemia (IDA) is the most common nutritional deficiency in childhood throughout the world. Although it has been shown that IRA is associated with elevated plasma copper and depleted zinc levels in children, there are conflicting results on the effect of iron supplementation on the absorption of these elements. The aim of this study was to investigate the effects of ferrous and ferric iron supplementation on the trace element status in children (n=25, aged 8-168 mo) with IDA. Fourteen of them wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 13 publications
2
30
1
Order By: Relevance
“…Sozmen et al . did not find any toxic effect of ferrous formulations on RBC and plasma in pediatric IDA patients . In the present study, TAOC level increased promptly in the PO group, while oxidative stress peculiar to IDA decreased.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Sozmen et al . did not find any toxic effect of ferrous formulations on RBC and plasma in pediatric IDA patients . In the present study, TAOC level increased promptly in the PO group, while oxidative stress peculiar to IDA decreased.…”
Section: Discussioncontrasting
confidence: 47%
“…Alterations in antioxidant state as a result of iron therapies via different dosage routes have not been elucidated fully. The absorption process after parenteral iron might last for at least 4 weeks and thus the generation of free radicals might be prolonged . Therefore in the present study the patients were followed until 13 weeks after termination of oral iron therapy, and blood samples were collected to measure these alterations.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have previously demonstrated that IPC achieves a significant increase in Hb levels in children with IDA [11, 12, 16–18]. The rate of the erythropoietic response to IPC appears to be dose dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies show superiority of Iron Polymaltose complex as treatment of iron deficiency anemia achieving a significant increase in Hb levels in children with IDA. [8][9][10][11][12] In a randomized trail of 49 iron deficiency anemic infants, Murahovschi et al found that with ferrous sulfate there was faster increase in Hb during the first month of treatment which then became slower after 1 month compared to those given Iron Polymaltose complex, both at a dose of 4mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%